DESCARTES’ OR RYLE’S MYTH? - Saulius, Tomas (Problemos, 2017)
In this paper, we treat Ryle’s The Concept of Mind as a polemical work. The main question is as follows. On what grounds does Ryle associate “an intellectual tendency” he criticizes with historical Descartes? We defend the following thesis: “the Myth of Descartes” is a rhetorical construction that does not reflect the main aspects of Descartes’ dualism. Two conclusions are drawn. First, without providing clear criteria for analysis, Ryle tries to give his work a systematic character through rhetorical means. Secondly, the contrasts between Meditations and “the Myth of Descartes” reveal that Ryle fails to give due reflection to his relationship with the philosophical tradition.
Keywords: Gilbert Ryle; Descartes; mind; dualism